Chlorophyll a fluorescence induction parameters of flag leaves characterize genotypes and not the drought tolerance of wheat during grain filling under water deficit - Guóth, Adrienn (Acta Biologica Szegediensis, 2009)
Chlorophyll a fluorescence induction parameters of two drought tolerant (MV Emese and Plainsman V) and two sensitive (GK Élet and Cappelle Desprez) wheat cultivars were compared on the day 16 post anthesis (DPA) under control and water stressed conditions. It was found that under drought stress the chlorophyll a (Chl ) content declined earlier in the sensitive genotypes, but the rate of Chl loss was much higher in the tolerant cultivars and also in the controls of cv. Plainsman after 12 DPA. The transzeatin content, a transport form of cytokinins also significantly declined to 16 DPA in the sensitive GK Élet. Because cytokinins prevent Chl loss, it may be a cause of the decreased Chl level in this cv. under drought. Neither net CO2 assimilation rate (PN) nor other Chl a fluorescence induction parameters such as Fv/Fm or φ PSII, qP and NPQ as a function of increasing photon flux densities (PFD) exhibited a special change which could characterize only tolerant or sensitive cultivars. Instead, these changes characterized the genotypes. In cvs MV Emese and Plainsman the flag leaf senescence could result in faster and better remobilization of the pre-stored carbon from vegetative tissues, and ultimately betteryield than in GK Élet and Cappelle Desprez under drought.